68Ga-DOTATATE and 68Ga-NODAGA-JR11 PET/CT Images in a Patient With Gastric Neuroendocrine Tumor. (25th October 2021) - Lin, Zefang; Lin, Rong; Zhang, Jiaying; Yao, Shaobo; Miao, Weibing
Abstract: A 52-year-old man with newly diagnosed gastric neuroendocrine tumor (NET) underwent 68 Ga-NODAGA-JR11 and 68 Ga-DOTATATE imaging. 68 Ga-DOTATATE PET/CT showed no 68 Ga-DOTATATE uptake in the lesion, where 68 Ga-NODAGA-JR11 showed intense uptake. The patient subsequently received endoscopic submucosal dissection and en bloc resection of the lesion, which was pathologically confirmed as gastric NET (G2). The positive findings of 68 Ga-NODAGA-JR11 in the current case highlighted that 68 Ga-NODAGA-JR11 PET/CT may be a promising molecular imaging technique for the detection of NETs with high sensitivity.